2018
DOI: 10.1002/cpph.44
|View full text |Cite
|
Sign up to set email alerts
|

Screening Strategies for the Discovery of Ion Channel Monoclonal Antibodies

Abstract: Ion channels play crucial roles in physiology by modulation of cellular functions that include electrical excitability, secretion, cell migration, and gene transcription. They are an important target class for drug discovery and have historically been targeted using small molecule approaches. A significant opportunity exists to target these channels with antibodies and alternative forms of biologics. Antibodies display high specificity, selectivity, and affinity for their target antigen, thus having the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 129 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…Indeed, antibodies, as protein entities, are known to be capable of changing protein conformation upon binding. A large amount of data exist showing that binding of IgGs to the protein can modify the conformation/structure of a protein [ 25 , 26 , 27 ]. Since an ion channel’s function depends directly on its spatial conformation, its interaction/insertion into lipid bilayer, its thermodynamic state, mono/tetrameric structure, and many more parameters/criteria, any binding to the protein channel in its natural, functional conformation will definitely induce a switch in ion channel conformation and thus activity [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, antibodies, as protein entities, are known to be capable of changing protein conformation upon binding. A large amount of data exist showing that binding of IgGs to the protein can modify the conformation/structure of a protein [ 25 , 26 , 27 ]. Since an ion channel’s function depends directly on its spatial conformation, its interaction/insertion into lipid bilayer, its thermodynamic state, mono/tetrameric structure, and many more parameters/criteria, any binding to the protein channel in its natural, functional conformation will definitely induce a switch in ion channel conformation and thus activity [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include flux-based assays that measure the cellular influx or efflux of radioactive Na + , Ca 2+ and Rb + for studying sodium, calcium and potassium channels, respectively, and fluorescence-based assays that utilize either voltage-sensitive dyes that measure cell membrane voltage changes or ion-specific fluorescent probes that measure changes in intracellular ion concentrations. 101 A recent and more detailed review of ion channel antibody screening strategies can be found in Colley et al 102…”
Section: Ion Channel Antibody Generation and Screeningadditional Consmentioning
confidence: 99%